2019
DOI: 10.1002/kin.21325
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic study of hydrogen sulfide decomposition on Pt(111) surface

Abstract: In this work, kinetic of H2S conversion to H2 molecule on the surface of Pt(111) is studied using kinetic Monte Carlo simulation. The results of simulation were fitted to the experimental temperature‐programed desorption spectra. The good agreement between the empirical and the simulated data confirms the proposed mechanism and kinetic data (activated energies and pre‐exponential factors). The influence of variables such as temperature and concentrations of H2S and H2 on the overall results of hydrogen product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…The optimized geometries and energies of the key structures along minimum energy paths (MEPs) were calculated, assuming the steps where * denotes active sites on the Au surface. These involve the adsorption of gaseous H 2 S (step 1), the sequential scission of two H–S bonds (steps 2 and 3), the associative desorption of gaseous H 2 (step 4), and the formation (step 5) and desorption (step 6) of S 2 , as generally accepted for H 2 S decomposition on metal catalysts. ,, The reaction initiates via the adsorption of H 2 S molecules on the photocatalyst surface with an adsorption energy of 0.60 eV (Figure a), matching well with experimental values of 0.4–0.5 eV . Both previous work , and our optimizations (Figure S6) show that the physisorbed H 2 S molecules attach to the Au(111) surface with an S atom on top of an Au atom.…”
supporting
confidence: 79%
“…The optimized geometries and energies of the key structures along minimum energy paths (MEPs) were calculated, assuming the steps where * denotes active sites on the Au surface. These involve the adsorption of gaseous H 2 S (step 1), the sequential scission of two H–S bonds (steps 2 and 3), the associative desorption of gaseous H 2 (step 4), and the formation (step 5) and desorption (step 6) of S 2 , as generally accepted for H 2 S decomposition on metal catalysts. ,, The reaction initiates via the adsorption of H 2 S molecules on the photocatalyst surface with an adsorption energy of 0.60 eV (Figure a), matching well with experimental values of 0.4–0.5 eV . Both previous work , and our optimizations (Figure S6) show that the physisorbed H 2 S molecules attach to the Au(111) surface with an S atom on top of an Au atom.…”
supporting
confidence: 79%
“…Mohamadi et al [27] in their published work found a similar result. They explored the effect of temperature on the adsorption rate of H2S on Pt anodes in a proton-exchange membrane fuel cell.…”
Section: Effects Of the Reaction Parameters And Their Interactions On...mentioning
confidence: 51%